Safe and effective removal of cyanoacrylate vascular access catheter securement adhesive in neonates - Hugill, Kevin; van Rens, Matheus F. P. T.; Alderman, Angela; Kaczmarek, Lori; Lund, Carolyn; Paradis, Amy (Frontiers in Pediatrics, 2023)
Neonatal vascular access continues to pose challenges. Recent times have seen considerable innovations in practice and the design and manufacture of materials used to provide infusion-based therapies with the intent to reduce the incidence and severity of vascular access related complications. However, despite these efforts vascular access-related complication rates remain high in this patient group and research evidence remains incomplete. In neonates, a medical grade formulation of cyanoacrylate adhesive is widely used to secure percutaneously inserted central venous catheters and is beginning to establish a role in supporting the effective securement of other devices like umbilical and peripheral intravenous catheters. This perspectives article considers issues specific to the removal of cyanoacrylate used to secure vascular access devices from neonatal skin before its bonding releases due to natural skin exfoliation processes. The aim of this information is to ensure safe and effective removal of octyl-cyanoacrylate adhesive-secured vascular access catheters from neonatal skin and stimulate professional discussion.